"To Me, It's Normal Journalism" Professional Perceptions of Investigative Journalism and Evaluations of Personal Commitment. (3rd July 2021) - Cancela, Pauline; Gerber, David; Dubied, Annik
ABSTRACT: This paper examines how professionals define investigative journalism, which criteria they use to assess their and others' work, and how they apply them. Based on 23 in-depth interviews with Swiss journalists, our research sheds new light on professionals' normative assumptions, and provides insights on how to think about investigative journalism more generally. Implicit and explicit professional definitions reveal a shared conception of journalism, which has strong normative implications. According to their narratives, professionals rely on a gradual and multilevel definition of investigative journalism, while often talking about it as an absolute. Rather than a discrete category, "investigative journalism" is best seen as existing on a continuum between full-fledged investigative endeavor and the most basic reporting, with the main cursor being the personal commitment: professionals value the extent of efforts provided during the investigative process, as much as other constitutive elements such as exposing breaches of public trust. They built on a mix of various elements regarding what constitutes investigative journalism. We distinguished three types of defining criteria: motive, extent of efforts and technique involved. These criteria counterbalance each other in practice. Arguably, these gradual conceptions allow for adjustments between a clear-cut ideal and the real work context.